The The Impact of Financial Behavior, Socioeconomic Status, and Academic Ability on Financial Literacy Among Students in Northern Kalimantan, Indonesia: The Moderating Role of Gender - Nur Islami, Rahmi (Manunggal Halim Jaya, 2025)
Financial literacy is one of the important competencies in dealing with the complexity of the modern economy. This study aims to analyze the factors that influence the financial literacy of students of the Faculty of Economics, Borneo University Tarakan, by considering the moderating role of gender. The research method used a quantitative approach with a survey involving 318 respondents. Data was analyzed using multiple regression tests and Moderated Regression Analysis (MRA). The results showed that financial behavior, socioeconomic status, and academic ability significantly positively affect financial literacy. In addition, gender acts as a moderator that strengthens the relationship between these variables and financial literacy. The findings confirm the importance of inclusive financial education strategies that consider socio-cultural factors to improve financial literacy among university students.